Anti-Fibrotic Effects of Low Toxic Microcystin-RR on Bleomycin-Induced Pulmonary Fibrosis: A Comparison with Microcystin-LR - Jie Wang; Jie Wang; Yan Ren; Yan Ren; Xiufen Zheng; Jiaqi Kang; Jiaqi Kang; Zhenqian Huang; Zhenqian Huang; Lizhi Xu; Lizhi Xu; Yaping Wang; et al. (Frontiers Media S.A., 2021)
Idiopathic pulmonary fibrosis (IPF) is a chronic progressive interstitial pulmonary disease characterized with radiographically evident pulmonary infiltrates and extracellular matrix deposition with limited treatment options. We previously described that microcystin-LR (MC-LR) reduces transforming growth factor (TGF)-β1/Smad signaling and ameliorates pulmonary fibrosis in bleomycin (BLM)-induced rat models. In the present study, we further demonstrate that microcystin-RR (MC-RR), an MC congener with lower toxicity than MC-LR, exerted an anti-fibrotic effect on BLM-induced pulmonary fibrosis rodent models and compared it with MC-LR. Our data show that MC-RR treatment attenuated BLM-associated pulmonary inflammation and collagen deposition in both therapeutic and preventive models. MC-RR reduced the expression of fibrotic markers, including vimentin, α-smooth muscle actin, collagen 1α1, and fibronectin, in rat pulmonary tissues. Furthermore, the core features of BLM-induced pulmonary fibrotic lesions were better alleviated by MC-RR than by MC-LR. MC-RR treatment substantially decreased the number of pulmonary M2 macrophages. In vitro, MC-RR attenuated the epithelial-mesenchymal transition and fibroblast-myofibroblast transition triggered by M2 macrophages. Therefore, we highlight MC-RR as a promising molecule for developing therapeutic and prophylactic strategies against IPF, a refractory lung disease.